The sculpting tool in bioprinting: research and application progress of sacrificial inks - Li Jing; Hai Ci; Zihan Zhang; Zhenxing Wang; Bin Wang (Frontiers in Bioengineering and Biotechnology)
The core of bio-3D printing technology lies in the development and optimization of bio-inks. For a long time, researchers have been looking for bio-inks that can balance printability and cell function. However, traditional bio-inks often have limitations in meeting this balance, limiting the complexity and scale of printable structures. In recent years, the emergence of sacrificial inks has brought a major breakthrough in this field, allowing bio-inks that were originally not very suitable for printing to accurately construct larger and more complex structures. This ink is unique in that it is used to support and position the bio-ink but is removed after printing is complete, not as part of the final printed structure. The mild nature of the state transition and removal conditions allows for minimal damage to cell viability and print structure when the ink is “sacrificed.” This review will focus on the types of sacrificial inks and their two key applications in bioprinting: building intracranial vascular networks and improving bioink performance. We will summarize the current status, advantages, and challenges of these applications, aiming to provide readers with a comprehensive overview of the latest advances in the use of sacrificial inks in bioprinting. By sacrificing the application of ink, bioprinting technology can not only produce more realistic and complex tissue structures but also is expected to provide broader application prospects for clinical treatment and regenerative medicine in the future.